Tactile mouse generating velvet hand illusion on human palm. (8th September 2016) - Rajaei, Nadar; Ohka, Masahiro; Nomura, Hironaga; Komura, Hiraku; Matsushita, Shojiro; Miyaoka, Tetsu
To enhance virtual reality (VR) generated by tactile displays, we have focused on a novel tactile illusion, called the Velvet Hand Illusion (VHI). In VHI, moving two parallel wires back and forth between the two hands leads humans to perceive a velvet-like surface between their hands. In earlier studies, we revealed that the intensity of VHI could be controlled by a ratio ( r / D ), where r and D are the wire stroke and wire distance, respectively. According to these findings, we investigate in this study whether a common tactile display is able to produce VHI, and whether the ratio can also control VHI intensity. We prepare a dot-matrix display as a tactile display in which moving one line of the display's pins is considered as a wire pattern. We investigate the VHI intensity with regard to changing the stroke r and the line distance D using paired comparison. Experimental results show that the VHI intensity is increased or decreased by changing r and D . We conclude that VHI can be created by the tactile display, and the intensity of VHI is controlled by changing the ratio of r / D .